Pervasive learning and its impact on cognitive development and learning of freestyle swimming skills in sports sciences students - Othman, Intisar Ahmed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The spread of the electronic system of knowledge among students and universities has led to the emergence of new forms of educational systems called pervasive learning. This is an educational system that uses wireless computer and telecommunications techniques, portable devices, and teaching techniques in an educational and training context and is an advanced system for the mobile learning system. The aim of this study was to prepare educational units with pervasive learning model to teach the basic skills of free swimming and also to identify the effect of pervasive learning model in learning free swimming skills. The researcher used the experimental study design. The research sample consisted of 20 students of the Faculty of Physical Education and Sports Sciences of Al Basrah University. The students were divided into two groups (10 students for the control group and 10 students for the experimental group). To achieve the objectives of the study, 5 tests about free swimming skills were performed. In order to analyze the data, T-test was used to analyze the differences between control and experimental groups for all free swimming skills tests. The results showed that there are statistically significant differences between the control and experimental groups in all free swimming skills tests, in favor of the experimental group (p<0.05). Through this study, it has been revealed that the educational units that used the pervasive learning model had a positive impact on the development of basic skills in free swimming.